1999
DOI: 10.1099/0022-1317-80-1-5
|View full text |Cite
|
Sign up to set email alerts
|

Scrapie strain-specific interactions with endogenous murine leukaemia virus.

Abstract: The finding that a senescence-accelerated mouse (SAMP8) shows early brain ageing, with histopathological changes resembling those seen in scrapie, combined with the discovery of high levels of endogenous murine leukaemia virus (MuLV) in brains of SAMP8 mice prompted us to examine the effect of scrapie infection on MuLV titres in this strain and in one of its progenitors, the AKR strain. Three scrapie strains (ME7, 22L and 139A) that had a comparatively short incubation period in SAMP8 and AKR mice caused an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…In the case of schizophrenia, however, the results are not unequivocal (14). In mice, there is also evidence of involvement of ERVs in spongiform encephalopathies (10). Thus, the higher expression of HERVs in the brain may have implications for susceptibility to neurological diseases and runs contrary to the apparent suppression of expression of even recent elements, such as GaLV in nonhuman primates.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…In the case of schizophrenia, however, the results are not unequivocal (14). In mice, there is also evidence of involvement of ERVs in spongiform encephalopathies (10). Thus, the higher expression of HERVs in the brain may have implications for susceptibility to neurological diseases and runs contrary to the apparent suppression of expression of even recent elements, such as GaLV in nonhuman primates.…”
Section: Discussionmentioning
confidence: 51%
“…Thus, at the DNA level, HERV evolution involves both vertical transmission and de novo integration of elements by retrotransposition or reinfection, whether looking within or among species (3,4,26). However, the majority of elements integrated before the OWM and great ape lineages diverged and thus have a similar genomic distribution pattern among catarrhines (16,10,27).…”
mentioning
confidence: 99%
“…One picomole of RNA was used, and the molar ratios of protein to nt are indicated at the top. Lanes 1,5,9,13,17 (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, PrP was shown to interact with sulfated glycans (12), RNA aptamers (13), and large nucleic acids (14,15), causing the formation of nucleoprotein complexes similar to HIV-1 nucleocapsid-RNA complexes formed in vitro (16). A recent report shows that MuLV replication accelerates the scrapie infectious process (17), suggesting possible in vivo interactions between retroviruses and PrP.…”
mentioning
confidence: 99%
“…Interestingly, recombinant prion protein has demonstrated the abilities to bind and to chaperone retroviral RNA, which are similar to retroviral nucleocapsid's function (18,19,42). Other interactions between prion protein and retroviruses have been identified; these interactions include an increase in murine leukemia virus (MLV) titers and replication and a shortened scrapie incubation period in the brains of coinfected mice (12,40). In vitro coinfection studies have also demonstrated increased scrapie infectivity release into the cell culture supernatant in murine cell cultures coinfected with MLV (39).…”
mentioning
confidence: 99%